Competition in mathematics as a form of educating gifted children: Kaunas case study - Dabrišienė, Vilija; Narkevičienė, Bronė (Lietuvos matematikos rinkinys, 2002)
The goal of this article is to disclose peculiarities of pedagogue's activities while preparing gifted students to participate in mathematical competitions and contests. The article presents the analysis of the situation in Kaunas. The given results are related to the research of the pedagogue attitudes towards educating gifted children, the pedagogue's teaching ways and methods and the dependence of the achievement of the participators of mathematical competitions on the type of school.The data of the research shows that the pedagogue attitudes are not favourable enough towards individualized education of giftted children. The individualization of giftted children in the secondary school is incomplete, the diversity in the modes of teaching activities is scarce and used episodically, this work is not planned, and it is not organized systematically. It is necessary to stimulate this activity of pedagogues and implement the system of motivation.